Os impasses nas funções parentais : da clínica psicanalítica do precoce às transformações sócio-histórico-culturais - Perfeito, Hélvia Cristine Castro Silva (2007)
This research had as its main objective analyse parental functions transformation in the clinical psycotherapeutical visits by both parent and child trying to stress the impasses in this functions, from a psycoanalytical and from a social cultural history. The family that is presented lately is shown in many different ways (reconstituted families) and it is upon the child and its tie to the parents, that rests the family continuity. There are substancial crises in the relations, mainly towards the father function, where crises of the symbolic references happens, as well as a growing mother centered family, which becomes horizontal and fraternal, going against the old model, in which we saw a vertical way with father centered families.Three clinical cases were analysed , from the infants psychopatology in the first infancy and the method used both for the development of the research and the analysis of the results was the psycoanalytical method. From the related analysts in each clinic cases, important datas were built upon the impasses experienced by comtemporary parents as: the parenting empting and change of location, associated with individualism and lolneliness, which are fundamental marks of the comtemporary subject; also feeling of insufficiency of parents associated to the simulacrum and with a masochistic way of relating to each other; the use of a psychic defensive mechanism denominated incorporation in which the lack of affection and the lowering of the reflexive, critycal and ellaborative capacity are present ; the use of a mechanisms of splitting as the way of dealing with the agony of the real ando f the pain; the use of a formal knowledge in the parent and child relationship against the everyday knowledge and the conception of the child symptoms as reactive to the neurosis of the parents by inter and transgeracional elements.